Germination characteristics and the relationship between population structure, soil seed bank density and fire response in the rare endemic Stachystemon vinosus (Halford & R.J.F.Hend.) (Euphorbiaceae) from southern Western Australia. Issue 2 (June 2019) - Vincent, Brian J.; Barrett, Sarah; Cochrane, Anne; Renton, Michael
Abstract: The regeneration niche defines the specific environmental requirements of the early phases of a plant's life cycle. It is critical for the long-term persistence of plant populations, particularly for obligate seeders that are highly vulnerable to stochastic events in fire-prone ecosystems. Here, we assessed germination characteristics and the relationship between population structure, soil seed bank density and fire response in Stachystemon vinosus (Euphorbiaceae), a rare endemic shrub from Western Australia, from burnt and long unburnt habitats. Many plants in long unburnt habitat were similar in size to those in recently burnt habitat. Soil seed bank density was related to plant abundance and fire history with density lower in burnt than unburnt sites. Thus, inter-fire recruitment may play a critical role in the requirements of the study species. To assess the dormancy status and germination requirements we used a 'move-along' experiment with temperatures from six seasonal phases of the year. Seeds were incubated under light and dark conditions, with and without smoked water, and with and without dry after-ripening. Germination was most effective when seeds were treated with smoked water and incubated in the dark at temperatures resembling autumn/winter conditions. After-ripening increased germination in light and dark incubated seeds in the absence of smoked water but was unnecessary for optimal germination in smoked water treated seeds. Irrespective of treatment, seeds showed a requirement for cooler temperatures for germination. These results suggest that rising temperatures and changes in fire regime associated with global warming may alter future germination responses of Stachystemon vinosus .